Adrenocortical Tumors and Pheochromocytoma/Paraganglioma Initially Mistaken as Neuroblastoma—Experiences From the GPOH-MET Registry - Kuhlen, Michaela; Pamporaki, Christina; Kunstreich, Marina; Wudy, Stefan A.; Hartmann, Michaela F.; Peitzsch, Mirko; Vokuhl, Christian; Seitz, Guido; Kreissl, Michael C.; Simon, Thorsten; Hero, Barbara; Frühwald, Michael C.; et al. (Frontiers in Endocrinology, 2022)
In children and adolescents, neuroblastoma (NBL), pheochromocytoma (PCC), and adrenocortical tumors (ACT) can arise from the adrenal gland. It may be difficult to distinguish between these three entities including associated extra-adrenal tumors (paraganglioma, PGL). Precise discrimination, however, is of crucial importance for management. Biopsy in ACT or PCC is potentially harmful and should be avoided whenever possible. We herein report data on 10 children and adolescents with ACT and five with PCC/PGL, previously mistaken as NBL. Two patients with adrenocortical carcinoma died due to disease progression. Two (2/9, missing data in one patient) patients with a final diagnosis of ACT clearly presented with obvious clinical signs and symptoms of steroid hormone excess, while seven patients did not. Blood analyses indicated increased levels of steroid hormones in one additional patient; however, urinary steroid metabolome analysis was not performed in any patient. Two (2/10) patients underwent tumor biopsy, and in two others tumor rupture occurred intraoperatively. In 6/10 patients, ACT diagnosis was only established by a reference pediatric pathology laboratory. Four (4/5) patients with a final diagnosis of PCC/PGL presented with clinical signs and symptoms of catecholamine excess. Urine tests indicated possible catecholamine excess in two patients, while no testing was carried out in three patients. Measurements of plasma metanephrines were not performed in any patient. None of the five patients with PCC/PGL received adrenergic blockers before surgery. In four patients, PCC/PGL diagnosis was established by a local pathologist, and in one patient diagnosis was revised to PGL by a pediatric reference pathologist. Genetic testing, performed in three out of five patients with PCC/PGL, indicated pathogenic variants of PCC/PGL susceptibility genes. The differential diagnosis of adrenal neoplasias and associated extra-adrenal tumors in children and adolescents may be challenging, necessitating interdisciplinary and multidisciplinary efforts. In ambiguous and/or hormonally inactive cases through comprehensive biochemical testing, microscopical complete tumor resection by an experienced surgeon is vital to preventing poor outcome in children and adolescents with ACT and/or PCC/PGL. Finally, specimens need to be assessed by an experienced pediatric pathologist to establish diagnosis.